Water use efficiency in grass species: Dactylis glomerata and Festuca arundinacea - Simões N.; Maçãs I.D.; Carneiro J.P.; Tavares de Sousa M.M. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
In order to evaluate water use efficiency (WUE), a field of perennial grasses -with several varieties/ecotypes of Dactylis glomerata and Festuca arundinacea- was established in Elvas, Portugal, in 2005-06. WUE, expressed in terms of dry matter yield per unit of water consumed, is important to understand the ability of plants to develop efficiently during the growing season (spring) and to define criteria to be used in plant breeding activities. The main hypothesis was to determine traits inducing high WUE during spring and earlier summer combined with traits determining high survival rates following dry summer periods. The measurement of biomass production is a possible indicator of WUE. The correlation between dry matter yield and WUE was variable and ranged from r=0.798 for Dactylis glomerata to 0.487 for Festuca arundinacea. Kasbah (Dactylis glomerata) had the lowest WUE; on the other hand, Porto was the opposite. In Festuca arundinacea the smallest WUE value was found in cv. Fraydo. Lutine (F. arundinacea) had the highest WUE. Festuca arundinacea had higher WUE than Dactylis glomerata.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)